Rhodium-catalysed carbon-carbon bond formation and carbon-sulfur bond functionalisation - Bouisseau, A (2017)
This thesis documents the development of synthetic methodologies utilising rhodium catalysis for the formation of carbon-carbon bonds and the functionalisation of carbon-sulfur bonds. Chapter 1 provides an overview of the two main areas of research discussed in this thesis that include the key developments in the field of intra- and intermolecular rhodium-catalysed hydroacylation, and the major advances in cross-coupling reactions via the catalytic cleavage of carbon-sulfur bonds. Chapter 2 details the development of a tandem rhodium-catalysed hydroacylation, sulfide elimination and subsequent enantioselective 1,4-conjugate addition sequence allowing the preparation of stereodefined β-substituted ketones. This process enables the formation of two carbon-carbon bonds and offers a general method to access highly functionalised traceless hydroacylation products. Chapter 3 describes the development of a rhodium-catalysed alkyne hydroacylation, thio-Michael addition sequence in a one-pot fashion. This methodology enables the synthesis of a variety of sulfur-containing heterocycles. Chapter 4 documents the efforts towards the development of a rhodium-catalysed cross-coupling reaction with alkenyl sulfides and boronic acids via C-S bond activation. This study explores both a tether-free and a traceless tether approach. Chapter 5 summarises the research and the potential future work. Chapter 6 provides experimental details and data.